The Fifth International Conference on Preservation of Digital Objects (iPRES 2008) - Alexander Ball; Michael Day; Manjula Patel (International Journal of Digital Curation, 2008)
The Fifth International Conference on Preservation of Digital Objects was held at the British Library on September 29â€“30, 2008, with the theme â€œJoined Up and Working: Tools and Methods for Digital Preservationâ€. Topics ranged from the technical foundations of digital preservation through preservation system architectures to the organizational and policy issues facing the custodians of digital resources. There were also sessions dedicated to dealing with particular types of content, training needs, and methods for auditing needs and services.